Modelling and optimization of surfactant sensor response characteristics for the use in surface water and wastewater analysis - Stanisavljev Ana Komanović; Grujić Aleksandra Perić; Bosnar Milan Sak (Zaštita Materijala)
The theoretical model of potentiometric titration curves of sodium dodecyl sulfate (anionic surfactant) was proposed and the response parameters of two surfactant sensors (commercial and self-made) were investigated. The both sensors were used to generate potentiometric experimental data, which were incorporated into the calculations using the mass and charge balance equations. The experimental data were compared with appropriate theoretical curves in which the sensor response parameters (sensor slope S, constant potential term Eo, potentiometric selectivity coefficient (K, pot i J), sensor's membrane parameter (solubility product constant KS, CatAn) and analyte properties (activity ai, concentration ci) were estimated and optimized with Solver (Excel).